Sleep Duration Change and its Associated Factors During Adolescence: a 6 Year Longitudinal Study - Yoo, Changmin (Child indicators research, 2020)
This study examined the developmental trajectory of sleep duration, and analyzed how this trajectory was associated with predictors among South Korean children. For these purposes, we used hierarchical linear modeling analysis involving 2257 subjects who participated in the Korean Children and Youth Panel Survey from 2010 to 2015 (i.e., ages 11, 12, 13, 14, 15, and 16 years; 50% girls). The results showed that sleep duration decreased over 6-years. Children with more time spent taking after-school classes and doing after-school homework had shorter sleep duration than their counterparts initially and these differences were maintained over time. When time spent on after-school classes and after-school homework increased by 1 h, sleep duration decreased by 0.071 h and 0.082 h, respectively. However, electronic media factors were not associated with the sleep duration trajectory. These results suggest that factors affecting children sleep may be different depending on the culture in which they live.